Acute Non-Contrast T1-weighted MRI Predicts Chronic Radiofrequency Ablation Lesions - Kholmovski, Eugene G. (J Cardiovasc Electrophysiol, 2018)
BACKGROUND: MRI has been used to visualize radiofrequency (RF) ablation lesions but the relationship between volumes that enhance in acute MRI and the chronic lesion size is unknown. OBJECTIVES: The main goal was to use non-contrast (native) T1 weighted (T1w) MRI and late gadolinium enhancement (LGE) MRI to visualize lesions acutely and chronically and correlate the acute area of enhancement with chronic lesion size in histology. METHODS: In a canine (n=9) model RF ablation lesions were created in both ventricles. Native T1w MRI and LGE-MRI were acquired acutely after the ablation procedure. After 8 weeks, another set of RF ablations was performed and the MRI study was repeated. Volume and depth of enhancement in native T1w MRI and LGEMRI acquired after the initial ablation procedure were correlated with chronic lesion volume and depth in histology. RESULTS: 33 lesions were analyzed. Native T1w MRI visualized the acute lesions but not the chronic lesions. LGE-MRI showed both acute and chronic lesions. Acute native T1w MRI volume (average of 102.1±48.5mm(3)) and depth (4.9±1.2 mm) correlated well with chronic histological volume (105.9±51.8mm(3)) and depth (4.8±1.3mm) with R(2) of 0.881, p<0.001 and 0.874, p<0.001 respectively. Acute LGE MRI had significantly higher volume of enhancement of 499.7±214.4mm(3) (p< 0.001) and depth of 7.5±1.8mm (p<0.001) compared to chronic histological lesion volume and depth. CONCLUSION: Native T1w MRI acquired acutely after RF ablation is a good predictor of chronic lesion size. Acute LGE-MRI significantly overestimates chronic lesion size.